A eficácia da teoria da responsabilidade civil para a resolução de casos complexos: análise do naufrágio do rebocador TBL CXX. - LISBOA, Ava Brígida Piza (Universidade Federal do Oeste do Pará, 2024)
This research consists of analyzing the effectiveness of the application of the Theory of Civil Liability in complex cases in the light of the case study of the shipwreck with the Tug Boat TBL CXX, an accident that occurred near Óbidos in August 2017. It was verified the technical use of civil liability applied in the case that will be studied, considering the incidence of reflex damage in relation to the victims, which identified the sufficiency of the use of theory for the solution of demand. In addition, it sought to identify whether the reparatory compensation for the damage caused to the victims met the rights, needs and expectations of family members. To respond to the problem formulated by this research, the following hypotheses are objectively, which, during the study, may or may not be confirmed: "the legal institute of civil liability contained in material law and applied to the case of the sinking of the TBL CXX tug was sufficient and met the needs and expectations of the victims/crew members' relatives" or "the legal institute of civil liability contained in material law and applied to the case of the sinking of the TBL CXX tug boat was not sufficient and met the needs and expectations of the victims'/crew members' families". These answers were obtained through qualitative research with the weighting and analysis of the contents obtained, as well as theoretical, that is, based on relevant and updated bibliography. Bibliographic methods were used, with doctrines, journal articles, magazines; documentary analysis of the legal techniques addressed throughout the application as the basis of civil liability and other petitions, based on the analysis of the judicial proceedings filed in the Federal and Labor Court, referring to the obligation to remove the tug from the bottom of the river and the civil reparation of the injuries suffered. A questionnaire was applied to the families of the deceased, in which questions were asked about the judicial process and their expectations regarding the compensation received and possible insatisms they have before the resolution of the lawsuit. As for the results obtained, it was found that the Theory of Civil Liability does not differ when applied in non-complex or complex cases, as well as is not effective in solving complex cases when analyzing the case of the sinking of the TBL CXX Tug, object of the present study.